Equal opportunity? Gender gaps in CEO appointments and executive pay - Matti Keloharju; Samuli Knüpfer; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2016)
This paper uses exceptionally rich data on Swedish corporate executives and their personal characteristics to study gender gaps in CEO appointments and pay. Both gaps are sizeable: 18% for CEO appointments and 27% for pay. At most one-eight of the gaps can be attributed to observable gender differences in executives' and their firms' characteristics. Further tests suggest that unobservable gender differences in characteristics are unlikely to account for the remaining gaps. Instead, our results are consistent with the view that male and female executives sharing equal attributes neither have equal opportunities to reach the top, nor are they equally paid.
Keywords: G34; J16; J24; J31; 330; CEOs; Compensation; Discrimination; Executives; Gender differences